Determining the Difference Between the Effects of Cognitive Behavioral Therapy-Based Therapeutic Intervention and Cognitive Behavioral Hypnotherapy on Anxiety and Depression in Military Personnel - Heydarian, Maryam; Afshari Nia, Karim; Amiri, Hasan (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aimed to compare the effectiveness of Cognitive Behavioral Therapy (CBT) and Cognitive Behavioral Hypnotherapy (CBH) in reducing symptoms of anxiety and depression among military personnel. Methods and Materials: The study employed a quasi-experimental design with a pre-test and post-test format, including a control group. Forty-five military personnel were recruited and randomly assigned to three groups: a CBT group (n=15), a CBH group (n=15), and a control group (n=15). The interventions consisted of eight 1.5-hour sessions over eight weeks. Anxiety and depression levels were assessed using the Depression, Anxiety, and Stress Scale (DASS-21) before and after the interventions. Data were analyzed using multivariate analysis of covariance (MANCOVA) to compare post-test scores while controlling for pre-test differences. Findings: The results indicated that both CBT and CBH significantly reduced anxiety and depression compared to the control group. However, participants in the CBH group showed greater reductions in anxiety and depression post-intervention than those in the CBT group. All four statistical tests (Pillai’s Trace, Wilks’ Lambda, Hotelling’s Trace, and Roy’s Largest Root) confirmed the significant effect of group membership on post-test scores. The effect size was larger for CBH, suggesting that hypnotherapy provided additional benefits in reducing emotional distress. Conclusion: Both CBT and CBH were effective in reducing anxiety and depression in military personnel, with CBH showing superior outcomes. Hypnotherapy’s ability to access subconscious cognitive and emotional processes may enhance treatment efficacy, making it a valuable tool for addressing mental health issues in high-stress populations like the military.